Nghiên cứu cơ chế phản ứng chuyển hóa CO2 bằng H2 trên xúc tác cluster Fe5 bằng phương pháp phiếm hàm mật độ - Điệp, Phạm Thị; Hà, Nguyễn Ngọc; Cầm, Lê Minh (Vietnam Journal of Chemistry, 2016)
CO2 hydrogenation over Fe5 cluster has been investigated by means of GGA-DFT method. As regards DFT, the Perdew–Burke–Ernzerhof (PBE) formalism for exchange and correlation was used. The obtained results showed that, the conversion of CO2 into HCOOH and HCHO is favourable while the formation pathways of CH3OH and CH4 are unfavourable. Keywords. Mechanism, pathway, activation energy, energy varies.